2014
DOI: 10.1093/neuonc/nou052
|View full text |Cite
|
Sign up to set email alerts
|

Germline rearrangements in families with strong family history of glioma and malignant melanoma, colon, and breast cancer

Abstract: BackgroundAlthough familial susceptibility to glioma is known, the genetic basis for this susceptibility remains unidentified in the majority of glioma-specific families. An alternative approach to identifying such genes is to examine cancer pedigrees, which include glioma as one of several cancer phenotypes, to determine whether common chromosomal modifications might account for the familial aggregation of glioma and other cancers.MethodsGermline rearrangements in 146 glioma families (from the Gliogene Consor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This could be tested using FISH and TP53 capture-based sequencing approaches for break point identification as in our study. Only a few cases have been reported where genomic structural alterations, usually deletions, cause cancer syndromes [ 32 39 ] and one study where a Robertsonian translocation results in a highly increased risk for childhood acute lymphoblastic leukemia with focal chromosome 21 amplification [ 40 ]. We present here a very rare phenomenon of a rearrangement hotspot which can give rise to both somatic rearrangements as well as a germline cancer syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This could be tested using FISH and TP53 capture-based sequencing approaches for break point identification as in our study. Only a few cases have been reported where genomic structural alterations, usually deletions, cause cancer syndromes [ 32 39 ] and one study where a Robertsonian translocation results in a highly increased risk for childhood acute lymphoblastic leukemia with focal chromosome 21 amplification [ 40 ]. We present here a very rare phenomenon of a rearrangement hotspot which can give rise to both somatic rearrangements as well as a germline cancer syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Primary malignant brain tumors are relatively rare; however, over the last few decades, it has been observed that the incidence rates for brain tumors have been increasing. This increase may be due to improved diagnostic techniques and to changes in tumor coding and classification [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence of brain tumors has modestly increased during the last few decades [4,5,6]. This tendency has been noticed mainly in benign tumors and it has been attributed to the improvement of diagnostic techniques and to changes in tumor coding and classification [4,6]. …”
Section: Introductionmentioning
confidence: 99%